Cell-Free DNA in Oncology: Gearing up for Clinic - Ulrich, Bryan C. (Ann Lab Med, 2018)
In the past several years, interest in the clinical utility of cell-free DNA as a noninvasive cancer biomarker has grown rapidly. Success in the development of plasma genotyping assays and other liquid biopsy assays has widened the scope of cell-free DNA use in research and the clinic. Already approved by the US Food and Drug Administration in the narrow context of epidermal growth factor receptor-mutated non-small cell lung cancer, plasma genotyping assays are currently being investigated in a wide array of clinical settings and modalities. These include plasma genotyping as a tool for early diagnosis, the detection of minimal residual disease, and the evaluation of treatment response/progression. In this review, we assess the clinical landscape of plasma genotyping assays and propose strategies for their further expansion into routine clinical care.